Influence of MO-GaN templates on the HVPE growth of semi-polar GaN thick films. Issue 18 (20th April 2021) - Zhang, Lin; Wu, Jiejun; Han, Tong; Liu, Fang; Li, Mengda; Zhu, Xingyu; Zhao, Qiyue; Yu, Tongjun
Abstract : This work illustrates the influence of MO-templates and competition mechanism on the HVPE growth of semi-polar GaN (11−22) & (10−13) thick layers. Abstract : In this paper, the growth of semi-polar GaN thick films was investigated on an m -plane sapphire by hydride vapor phase epitaxy (HVPE). By optimizing parameters of the HVPE process, both (11−22) and (10−13) semi-polar GaN films have been successfully obtained with a mirror surface and excellent crystal quality on different GaN templates grown by metal organic chemical vapor deposition (MOCVD), respectively. The influence of MO-GaN templates on the HVPE growth was further studied. The results revealed that the same plane of a semi-polar HVPE-GaN thick layer was grown on a single-phase template, such as GaN (11−22)HVPE on (11−22)MO-template and GaN (10−13)HVPE on (10−13)MO-template . However, on mixed-phase MO-templates, a single-phase (11−22) GaN thick layer was found to grow even if the original templates contain both (11−22) and (10−13) plane components. Meanwhile, in contrast with the difficult growth of GaN (10−13) with a smooth surface, it is easier to acquire GaN (11−22) thick layers by a HVPE method. A wider window for the growth of the (11−22) plane could partly explain the reason why the pure GaN (11−22) plane could be grown on mixed-phase ((11−22) & (10−13)) MO-templates. In order to explain this phenomenon, both formation energy ( E f ) and migration barrier ( E m ) of these semi-polar faces were calculated. Our results indicated that the E f of GaN (10−13) (−0.56 eV) is higher than that of (11−22) (−10.73 eV), and the E m of (10−13) (0.30 eV) is lower than that of (11−22) (1.89 eV). So the (11−22)-plane growth was more likely to be prevalent in competition between two phases.